Drought Risk Reduction Efforts in The Village of Krendowahono Gondangrejo Karanganyar Using Geolistric Surveys - Sorja Koesuma; Budi Legowo; Darsono Darsono; Iwan Yahya; Harjana Harjana (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Krendowahono, Gondangrejo, Karanganyar regency is located in the north of Surakarta city which is in 2019 the most affected area of drought. During August 2019 to November 2019, the village needs 2 to 5 water tanks dropping per day with a capacity of 5000 liters per tank. With such drought conditions, the villages government should provide clean water for their citizens. The method used for determining groundwater aquifers is the Geoelectric Method. This method works by injecting an electric current into the ground surface, then measuring the potential difference. Based on the obtained resistivity value, it can be interpreted at what depth there are groundwater aquifers. At the geoelectric survey location in Krendowahono village, it was found that the groundwater aquifer might be in layer 5 at a depth of 92.3 meters below, but the groundwater potential at this layer was not huge enough. Potential aquifers are likely to be from a depth of 92.3 meters to 110-120 meters.